Prevalence, withdrawal symptoms and associated factors of khat chewing among students at Jimma University in Ethiopia - Tilahun Abdeta; Daniel Tolessa; Kristina Adorjan; Mubarek Abera (BMC Psychiatry, 2017)
Abstract Background Recently, khat chewing has become a common practice among high school, college, and university students. Regular khat chewing is thought to be a predisposing factor for different physical and mental health problems. It can lead to absenteeism from work and classes. In Ethiopia, to our knowledge no published study has investigated khat withdrawal symptoms. Therefore, this study was conducted to determine the prevalence, withdrawal symptoms, and associated factors of khat chewing among regular undergraduate students on the main campus of Jimma University in Ethiopia. Methods The institution-based, cross-sectional study was conducted in January 2016. Data were collected from 651 main campus regular undergraduate students with a structured, self-administered questionnaire, entered into Epidata 3.1 and exported to SPSS version 20 for Windows. Bivariate and multivariate logistic regressions were used to explore associations and identify variables independently associated with khat chewing. Results The study found that the lifetime and current prevalence of khat chewing among students were 26.3% (95% CI: 24.3, 28.3) and 23.9% (95% CI: 21.94, 25.86), respectively. About 25.7% of students started chewing after joining university, and 60.5% of these students started during their first year. The main reason given for starting khat chewing was for study purposes (54.6%), followed by socialization purposes (42.3%). Among current khat chewers, 72.9% reported that they had chewed khat for 1 year or more and 68.2% reported that they had experienced various withdrawal symptoms. The most frequently reported withdrawal symptoms were feeling depressed, craving, and feeling fatigued. Being male, attending a place of worship daily/2–3 times per week, cannabis use, smoking cigarettes, and having family members currently chewing khat were independently associated with khat chewing. Conclusions This study found that large numbers of university students were currently chewing khat. In this study withdrawal symptoms and factors that significantly affect khat chewing were identified. Besides it gave new ideas regarding khat withdrawal symptoms in Ethiopia. It serves as a critical role of providing information to form rational foundation for public health policy, prevention and planning to bring change in contributing factors for Khat chewing. The finding will be serving as base line information for further study.